Pembelajaran Kata Benda Melalui Analisis Teks Deskriptif Pada Siswa Kelas 7 MTS Lijamul Athfal Sukabumi - Maguna Eliastuti; Irnawati Irnawati; Ana Rusmardiana; Tri Astuti (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Education in Indonesia plays an important role in the development of individuals and the country, shaping social and cultural values and preparing for the future. Quality education creates human resources who are innovative and have high social awareness, as regulated in Republic of Indonesia Law no. 20 of 2003. The main challenge is to maintain achievements and adapt to the Society 5.0 era. Curricula, such as the 2013 Curriculum and the Merdeka Curriculum, are designed to develop students' knowledge, skills and character. English as a compulsory subject increases career and educational opportunities in the context of globalization. English teaching in Indonesia emphasizes listening, speaking, reading and writing skills, as well as the importance of grammar and vocabulary. Nouns are an important element in sentence formation, and understanding nouns helps students in all aspects of language skills. An effective method for studying nouns is through descriptive text analysis. The Community Service Activity (PKM) entitled "Learning Nouns Through Descriptive Text Analysis for Grade 7 Students at MTs Lijamul Athfal Sukabumi" aims to develop community potential, increase creativity, writing skills and relationship networks. It is hoped that this PKM can improve students' understanding of nouns and become a guide for language learning in Indonesian literature, as well as arouse interest in learning English. The method used includes preparation and implementation of noun learning through descriptive text analysis at MTs Lijamul Athfal Sukabumi with results showing high enthusiasm from students. It is hoped that this fun context-based learning can be an alternative that advances education and produces students with international insight.